Arrest of trans-SNARE zippering uncovers loosely and tightly docked intermediates in membrane fusion - Yavuz, Halenur (J Biol Chem, 2018)
Soluble N-ethylmaleimide–sensitive factor attachment protein receptor (SNARE) proteins mediate intracellular membrane fusion in the secretory pathway. They contain conserved regions, termed SNARE motifs, that assemble between opposing membranes directionally from their N termini to their membrane-proximal C termini in a highly exergonic reaction. However, how this energy is utilized to overcome the energy barriers along the fusion pathway is still under debate. Here, we have used mutants of the SNARE synaptobrevin to arrest trans-SNARE zippering at defined stages. We have uncovered two distinct vesicle docking intermediates where the membranes are loosely and tightly connected, respectively. The tightly connected state is irreversible and independent of maintaining assembled SNARE complexes. Together, our results shed new light on the intermediate stages along the pathway of membrane fusion.